Toxicity potential of denture adhesives: A scoping review - Costa, Rayanna Thayse Florêncio; Barbirato, Davi da Silva; Santiago Junior, Joel Ferreira; Barros, Maria Cynésia Medeiros de; Pellizzer, Eduardo Piza [UNESP]; Moraes, Sandra Lúcia Dantas (Elsevier, 2021)
Statement of problem: Denture adhesives are widely used products, but limited evidence regarding their toxicity is available. Purpose: The purpose of this scoping review was to map the existing literature on the toxic potential of denture adhesives. Material and methods: This scoping review was structured based on the 5-step methodology proposed by Arksey and O'Malley and The Joanna Briggs Institute Manual for Evidence Synthesis and followed the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews. The methods were registered on the Open Science Framework (<osf.io/nqryt>). The following research question was formulated: Are there any toxic effects related to the use of denture adhesives? The electronic literature search was performed independently by 2 authors in the following databases: PubMed/MEDLINE, Scopus, Web of Science, and the Cochrane Library. The inclusion criteria were in vitro and clinical studies; studies that evaluated the cytotoxic properties of denture adhesives as local or systemic implications; and studies published in English. Results: The search conducted in October 2020 provided 1099 articles. In total, 33 studies were included, 14 in vitro and 19 clinical studies. Commercially available denture adhesives have a dose-dependent cytotoxic effect on fibroblasts and keratinocytes, with poor cell recovery noted in older human fibroblasts. Patients presented different levels of neurologic or hematological alterations associated with the excessive use of denture adhesives. Conclusions: Most commercially available denture adhesives have a dose-dependent cytotoxic effect, and the use of well-adapted removable dental prostheses, proper patient follow-ups, and correct instructions for their use when indicated should be a priority.